(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The study aimed to identify the hidden meaning lying behind the text of two Malaysian Online newspapers i.e. ‘Malaysiakini’ (alternative newspaper) and ‘The New Straits Times’ (mainstream newspaper). The language of the newspaper always depicts its ideology through its stances. To discover the stances of newspapers, Martin and White (2005) ‘Appraisal Analysis’ framework was employed on 5 news reports (3,265 words) from ‘Malaysiakini’ and 3 news reports from ‘The New Straits Times’ (2,456 words) which were based on the performance of social actors during the 17th and 18th August 2018. It has been found that Pakatan Harapan (PH) government (Dr.Mahathir) was represented the most in both newspapers as compared to the Barisan Nasional (BN) as an opposition who lost the election in 2018, the very first time after independence. By ‘Appraisal Analysis’ it is found that both newspapers have represented Dr. Mahathir the most by positive attitudinal results in ‘Appreciation’ resource as ‘Malaysiakini’ has shown 37%, while; ‘NST’ given 56% positive attitudinal instances being a governmental influenced newspaper.